2004
DOI: 10.1523/jneurosci.1219-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Odorant Receptor Expression Patterns Are Restored in Lesion-Recovered Rat Olfactory Epithelium

Abstract: Lesions of the olfactory periphery provide a means for examining the reconstitution of a diverse and highly regulated population of sensory neurons and the growth, en masse, of nascent axons to the bulb. The olfactory epithelium and its projection onto the bulb are reconstituted after ablation by methyl bromide gas, and some measure of olfactory function is restored. The extent to which the system regenerates the full repertoire of odorant receptor-expressing neurons, particularly their spatially restricted di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
112
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 50 publications
11
112
0
Order By: Relevance
“…Similar regulation may also occur during regeneration after lesion to the olfactory epithelium, because the recovered OR expression pattern closely resembles that in the control animals (Iwema et al, 2004). The developmental trajectories of the OR expression patterns may be modified by the postnatal (or even prenatal) chemical environment.…”
Section: Differential Developments Of Osns Expressing Different Orsmentioning
confidence: 66%
“…Similar regulation may also occur during regeneration after lesion to the olfactory epithelium, because the recovered OR expression pattern closely resembles that in the control animals (Iwema et al, 2004). The developmental trajectories of the OR expression patterns may be modified by the postnatal (or even prenatal) chemical environment.…”
Section: Differential Developments Of Osns Expressing Different Orsmentioning
confidence: 66%
“…There is one possibility that these results are correlated with the localization of particular olfactory receptors. It has been reported that several olfactory receptors were expressed in the restricted region of the rat nasal cavity [24,42], and that olfactory receptors OR14 and OR16 were expressed in the olfactory epithelium lining dorsomedial region of the rat nasal cavity [24]. Therefore, eNOS protein may be expressed more intensely in the olfactory cells expressing OR14 and OR16 than in those cells expressing other receptors.…”
Section: Discussionmentioning
confidence: 98%
“…These observations are relevant to the recovery of individual neuronal populations observed in ␤3GnT1 null mice, in which, despite the widespread reexpression of lactosamine, the population of P2 and I7 odorant receptor neurons decreased postnatally until Ͻ15% of the normal number remained in adults. One possibility is that variations in sensory experience attributable to differences in environmental odor ligand exposure could lead to variations in recovery, a hypothesis previously suggested from chemical lesioning models of olfactory regeneration (Iwema et al, 2004). It is also possible that some subsets of sensory neurons are unable to de novo express lactosamine during the regeneration phase.…”
Section: Discussionmentioning
confidence: 98%
“…Digoxigenin-labeled riboprobes (Roche Applied Science, Indianapolis, IN) were synthesized and hybridized to 4% paraformaldehyde-fixed, cryosectioned tissue as described previously (Henion et al, 2001). Odorant receptor riboprobes, prepared according to Iwema et al (2004), were provided by Dr. James Schwob (Tufts University, Boston, MA).…”
Section: Methodsmentioning
confidence: 99%